2021
DOI: 10.3390/electronics10131539
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Machine Learning-Based Energy-Efficient Routing Algorithms in Wireless Sensor Networks

Abstract: Machine learning (ML) technology has shown its unique advantages in many fields and has excellent performance in many applications, such as image recognition, speech recognition, recommendation systems, and natural language processing. Recently, the applicability of ML in wireless sensor networks (WSNs) has attracted much attention. As resources are limited in WSNs, identifying how to improve resource utilization and achieve power-efficient load balancing is becoming a critical issue in WSNs. Traditional green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 80 publications
(124 reference statements)
0
17
0
Order By: Relevance
“…Wireless sensor networks [78] In this article, the authors investigated and proposed a theoretical hypothetical model of wireless sensor networks as an effective method for creating an energy-efficient green routing model that can overcome the limitations of traditional green routing methods. For comparison, the authors built several wireless sensor networks and tested attacks on them, after which they applied machine learning to determine the probability of attacks.…”
Section: Name Of the Property Publication A Brief Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wireless sensor networks [78] In this article, the authors investigated and proposed a theoretical hypothetical model of wireless sensor networks as an effective method for creating an energy-efficient green routing model that can overcome the limitations of traditional green routing methods. For comparison, the authors built several wireless sensor networks and tested attacks on them, after which they applied machine learning to determine the probability of attacks.…”
Section: Name Of the Property Publication A Brief Descriptionmentioning
confidence: 99%
“…Analyzing the sources of the above table, we can say that in [69,78,80,83,85,86] the authors built schematic models to demonstrate their usefulness, and in [71,[73][74][75][76][77]81,82,84,[87][88][89][90] the authors cited models either existing, described in words or only mathematically. This approach may not be clear to everyone, and may also cause difficulties.…”
Section: Name Of the Property Publication A Brief Descriptionmentioning
confidence: 99%
“…e experiments demonstrated that the Q-routing strategy can efficiently avoid the network congestion and minimize the packet transmission time when compared to standard shortest path routing. However, although many subsequent works have perfected and optimized the method [17,18], limited by the computing power of the router and the design of the network layer structure, the intelligent routing algorithm is difficult to be deployed in real network scenarios.…”
Section: Overview Of Intelligent Routing Algorithmsmentioning
confidence: 99%
“…[36] Path creation Flow-based Centralized Ref. [16][17][18][19][20][21] Path creation Packet-based Online Decentralized Online Ref. [14] Splitting ratio configuration Epoch-based Centralized Ref.…”
Section: Utilize Intelligent Modules To Assist Routing Calculationmentioning
confidence: 99%
See 1 more Smart Citation